Feasibility studies on Teruntum Complex, Kuantan / Noor Kamisah Abu Bakar - Abu Bakar, Noor Kamisah (2001)
The actual condition of Teruntum Complex, unfortunately shows a significant drawback of retailers, customers and thus contribute to maximum loss of profit, for the once popular shopping complex in Kuantan, Pahang. The needs to outlined the aspects of feasibility studies become the main intention of this dissertation, as clearly defined from the title of the dissertation “Feasibility Studies On Teruntum Complex, Kuantan”. Chapter 1 of this dissertation contains the introduction of this dissertation, including the objectives, issues, scopes and research method. Background studies will be featured in Chapter 2 which emphasise several background research as general review on the feasibility stua.es and shopping complex development in Malaysia. Aspects on market studies that emphasise the evaluation on the surrounding area of Kuantan is the main topic of Chapter 3. The aspects of the market studies include the study on the competitors, socio-economic and site potential, as well as other related aspects. Chapter 4 contains the aspects of feasibility studies on Teruntum Complex, which focus on the existing condition of this shopping complex, including all details on previous aims and future plans. Chapter 5 is a compilation of analysis and reviews based on the studies as reveal in Chapter 3 and Chapter 4; while Chapter 6 is the conclusion of the dissertation’s title and topic with additional section on recommendations.